Avaliação dos parâmetros físico-químicos da água do arroio Fonte do Mato, no município de Caçapava do Sul - RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Water is a fundamental natural resource for life. Drinking water is the resource that falls within the acceptable physicochemical standard for human consumption. Pro-blems related to the quality of water resources may be linked to anthropogenic misu-se, where domestic and industrial wastes are rampant in the environment, as well as the use of agricultural defenders, dissolve in water, seep into the soil. Another form of contamination of water bodies is from the contact of sediments with water, which may contain contaminants, which are generated by weathering and erosion of rocks. The municipality of Caçapava do Sul is located in the south central region of the state of Rio Grande do Sul, and a study area is located within the urban perimeter of the mu-nicipality. The scope of this work is a hydrochemical characterization of surface water use, collected for a long time at the Arroio do Mato Fountain, seeking to identify the types of contaminants present. Chemical chemical methods were used: turbidity, electrical conductivity, pH, total solids, dissolved oxygen, biochemical oxygen de-mand, total phosphorus, nitrate and total coliforms. Among the physicochemical methods analyzed, the turbidity indexes, ST, OD, BOD, TF and total coliforms, which were considered major non-conformities with the measures of the Ministry of Health and CONAMA. Regarding the classification, Arroio Fonte do Mato Water belongs to CONAMA Class I, does not exhibit power standards (according to PRC No. 5/2017, Annex XX), before being subjected to an appropriate treatment.
Keywords: Hidroquímica; Águas superficiais; Contaminantes; Hydrochemistry; Surface water’s; Contaminants; CNPQ::CIENCIAS EXATAS E DA TERRA